2017
DOI: 10.1590/s1806-92902017000900008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chamomile extract on the welfare of laying Japanese quail

Abstract: -The objective of this study was to evaluate the effect of chamomile extract on Japanese quail on their performance, animal behavior, tonic immobility, body injuries, and surface temperature. The trial was conducted using 108 quail distributed in a completely randomized experimental design, with three treatments (0, 2.5, and 5.0 g chamomile/kg of feed), six replicates, and six birds per treatment, evaluated in six measures repeated in time (14, 28, 42, 56, 70, and 84 days of trial). The inclusion of chamomile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Adult quails increase interaction (aggressive or non-aggressive) as a result of regrouping with the aim of restoring the hierarchy of the group formed (Guzmán et al, 2013). This phenomenon occurs mainly within the first 24 hours after exposure of birds to such social stress (Tenório et al, 2017) or in the first week (Guzmán et al, 2013). Therefore, the greater expression of pecking and riding behaviors may be the result of the adaptation period of these birds until they reestablish the group hierarchy.…”
Section: Resultsmentioning
confidence: 99%
“…Adult quails increase interaction (aggressive or non-aggressive) as a result of regrouping with the aim of restoring the hierarchy of the group formed (Guzmán et al, 2013). This phenomenon occurs mainly within the first 24 hours after exposure of birds to such social stress (Tenório et al, 2017) or in the first week (Guzmán et al, 2013). Therefore, the greater expression of pecking and riding behaviors may be the result of the adaptation period of these birds until they reestablish the group hierarchy.…”
Section: Resultsmentioning
confidence: 99%
“…These results also agreed with Abd El-Galil et al (2011); Attia (2018) who observed a significant improvement in FCR for the treatment with dietary CFP. Inversely, several previous studies did not record any significant effects on FCR due to supplementing laying diets with chamomile (Abaza, 2007;Abu Taleb et al, 2008;Tenório et al, 2017 andBehnamifar et al, 2018). No mortality was recorded among all treatments in the present study, and this may be due to the CFP and/or its bioactive components as a promising feed additive used in this experiment.…”
Section: Resultsmentioning
confidence: 89%
“…However, Abd El-Galil et al (2010); Galib and Khalel (2011) and Pandian et al (2013) who stated that supplementation of chamomile to laying Japanese quail or Rhode Island Red chickens diets, respectively, significantly increased FC in comparison with the control. Several previous studies did not record any significant effects on FC due to supplementing laying diets with chamomile (Abu Taleb et al, 2008;Marques et al, 2010 andTenório, et al, 2017). Regarding the FCR, ducks fed diet supplemented with 1 g CFP/kg (T2) had the lowest value (P≤0.05) of FCR in comparison with the other groups, it was observed that T2 improved FCR by about 9.5 and 22.0% as compared to the control group during the periods 31-35 and 35-39 weeks of age, respectively as shown in Table 2.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Chamomile is characterized as low -growing apple scent expressing its Greek name Chamos (ground) and melos (apple) [7]. It presents a pleasant taste with various medicinal effects including anti-inflammatory, anticancer (skin, breast, ovarian, or prostate), antioxidant, antiphlogisitis, treatment of wound, acute viral nasopharyngitis (known as common cold), infant colic disorder, haemorrhoids, mucositis, osteoporosis, vaginitis, improving cardiac health, managing diabetes, sleep, sedation, anxiety, seizure, eczema, digestive disorders, diminishing hyperglycaemiarelated oxidative stress, and others [1,8,9]. Numerical Taste predication (Table (1), Figure (2)) confirmed sour probability of the tested constituents ranged (o.537-1) for bitter, (0.546-0.989) for sweet, and (0.834-1) for sour character.…”
Section: Resultsmentioning
confidence: 99%